Effectiveness of Various Oral Feedback Techniques in CALL Vocabulary Learning Materials - (:unkn) unknown (ANI YAYINCILIK, 2009)
Problem Statement: When using Computer Assisted Language Learning (CALL) materials for individual study, it is crucial for learners to be able to monitor and evaluate their own learning processes. The feedback provided by these materials plays an important role in supplying this relevant information to the learner. However, results of previous studies are inconsistent, especially in considering if providing the correct response is beneficial or counterproductive. Some studies argue that, for verbal information, providing the correct response could be effective as it adds information to the mental structures of the learner. Purpose of Study: The current study investigates the effects of different combinations of verbal oral feedback in CALL vocabulary materials. Although new materials enhanced with artificial intelligence and simulations are being developed, the focus here is on traditional CALL materials. There are two main reasons for this. Primarily, these are affordable self-study materials used to increase and reinforce meaning and pronunciation of foreign language vocabulary. These materials, which feature game-like activities, specifically suit primary school learners with limited targets for learning. Additionally, most schools in Turkey already possess such materials. However, the approach to feedback in these materials is inconsistent and deserves more attention. Methods: A pre-test, post-test experimental design was used to analyse the effects of different types of oral feedback techniques on the number of words recalled. The study group consisted of sixth and seventh grade students from different schools in Istanbul, Turkey. Study materials only differed in their approach to feedback in the practice stage. Findings and Results: The study tested various conditions which differed in oral feedback used in the materials. Results indicate that explanatory feedback is more effective than confirmation feedback. However, findings also suggest that confirmation feedback could be equally effective when other feedback variables, such as trial number and repeating each question, are manipulated. In contrast to what the literature has suggested, this study demonstrated a surprising result: written feedback did not increase the effectiveness of verbal oral feedback. An animation technique, using a flashing animation was found to be more influential than written feedback in strengthening attention, perception, and word association. Conclusions and Recommendations: The best practices for using oral feedback in CALL vocabulary materials include paying attention to the amount of time allocated after the oral feedback of a correct response, using animation to enhance the effectiveness of a correct response and the effects of repetition, number of trials and audio-visual cues.
Keywords: Oral feedback; feedback types; feedback techniques; vocabulary; CALL